2022
DOI: 10.1017/s0033291722003099
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the evidence on inflammation in depressive illness and symptoms in chronic and end-stage kidney disease

Abstract: Background Depression affects approximately 27% of adults with chronic kidney disease (CKD) and end-stage kidney failure (ESKF). Depression in this population is associated with impaired quality of life and increased mortality. The extent of inflammation and the impact on depression in CKD/ESKF is yet to be established. Through a systematic literature review and meta-analysis, we aim to understand the relationship between depression and inflammation in CKD/ESKF patients. Methods We searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…It is observed that inpatients diagnosed with MDD (IMDD), the majority of whom suffer from very severe MDD and melancholia, exhibit indications of an immune response, including activation of M1 macrophages, T helper (Th)1, Th2 and Th17 immune cells, and an acute phase response with increased levels of acute phase proteins, complement factors, and pro-inflammatory cytokines, e.g., interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α [13]. These findings have been extensively replicated and published in various meta-analyses [48].…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that inpatients diagnosed with MDD (IMDD), the majority of whom suffer from very severe MDD and melancholia, exhibit indications of an immune response, including activation of M1 macrophages, T helper (Th)1, Th2 and Th17 immune cells, and an acute phase response with increased levels of acute phase proteins, complement factors, and pro-inflammatory cytokines, e.g., interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α [13]. These findings have been extensively replicated and published in various meta-analyses [48].…”
Section: Introductionmentioning
confidence: 99%
“…Psychological problems are also very frequent in these patients, presenting a prevalence of depression of 27%, which is associated with impaired quality of life and increased mortality. Besides, there is evidence of an association of higher pro-inflammatory and lower anti-inflammatory cytokine levels and depressive symptoms in patients with CKD/CKF [28]. In this sense, exercise offers great benefits to improve both inflammatory levels and associated depressive symptoms [18,29].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, research involving patients on substitution therapy reported that lower levels of IL-10 were associated with depressive symptoms [ 23 ]. A recent meta-analysis of end-stage CKD [ 24 ] found that subjects with depressive symptoms had a pattern of elevated proinflammatory IL-6 and low concentrations of anti-inflammatory IL-10. These authors ascribed the discrepant results between studies to heterogeneity in the analyses and to some individuals’ previously observed genetic proneness to an increased inflammatory response [ 23 ].…”
Section: Introductionmentioning
confidence: 99%